(untitled) (Research, Society and Development, 2020)
This paper was conducted with the aim of understand how the psychodynamic of work (POW) is present in the context of resocialization of patients with mental disorders through work in a foundation which connects health, arts and popular culture. Five semi-structured interviews were conducted at a foundation with two types of workers: i) three users with mental disorders; and ii) two worker-caregivers. Through a qualitative approach, we used the methodology for the analysis of nuclei of meaning (ANS) to understand the data in which they were all transcribed and analyzed in the Atlas Ti software. 383 nuclei of meaning were found and grouped into six themes related to dimensions context and content of the PDT: i) working conditions; ii) work organization; iii) labor relations; iv) pleasure-suffering; v) defense strategies; vi) recognition. Lastly it was possible to conclude that: i) the work in this enterprise besides help in the resocialization also beneficially contributes in the psychological treatment of the patients; and ii) with regards to the “workers-caregivers”, they have relearned their own work from the action of the “workers-patients”, forming a network of multifaceted relationships.